Alagamentos e inundações relacionados à qualidade física dos solos nas áreas de preservação permanentes urbanas - Schmitt, Gilberto (2014)
In recent years Brazil has been hit by numerous natural disasters on the phenomena of hydrological nature, like floods and spates. The Urban Conservation Units, known as Municipal Natural Parks, have as main objectives to protect water resources and soil. Among several measures to prevent the risks and vulnerabilities related to these hydrological events, the Municipal Natural Parks of Curitiba was one of the alternatives designed to reduce the problems caused by floods and spates. The Parks aims to maintain the biological diversity of flora and fauna native to the area, preserve the natural ecosystem, restore degraded ecosystems, promote environmental education and provide the means for scientific research. The objective of this study is to make a diagnosis of the physical quality of the soil of Permanent Preservation Areas of the Municipal Natural Park Tanguá, Tingui and Barigui and linking the risks and vulnerabilities related to floods and spates from these analyzes. The aforementioned parks form the largest municipal linear park in Brazil. Soil samples were collected in three different areas of Tanguá Parks, Tingui and Barigui. The results obtained in the Park Tanguá soils had compression on all sampling areas, so these soils do not meet their functionality in reducing risk to floods and flooding. The areas sampled in Tingui and Barigu Parks expressed characteristics that favor infiltration and the development of native vegetation in APPs. These data will be used by the Municipal Department of the Curitiba Environment to assist in environmental management of Urban Conservation Areas, both in Biocidade Project as the Department of Municipal Risk Management Environment of Curitiba.